Dynamic identification and FE updating of S. Torcato Church, Portugal - Ramos, Luís F. (2011)
San Torcato Church is located near the city of Guimarães, Portugal. The construction of the church started in 1871 and completed in recent years. The church combines several architectonic styles, like Classic, Gothic, Renaissance and Romantic. This “hybrid” style is also called in Portugal as “Neo-Manuelino”. At the moment, the church has significant structural problems due to soil settlements of the main façade. Cracks can be observed in the main and lateral facades. The cracks are visible from the outside and inside of the temple. The bell-towers are leaning, and the arches in the main nave present vertical deformations. Non-stabilized phenomena are present in the structure. To stabilize the damage, a structural intervention is planned to occur soon and the church is already monitored to assist the intervention. The paper clearly presents the problem with emphasis to the dynamic analysis carried out before the structural strengthening, namely: the experimental tests with output-only techniques for frequencies, damping and mode shapes estimation, and FE model updating analysis.